(untitled) (Damu Journal of Sport Sciences, 2024)
The study aimed to identify the effect of different scoreboard heights on learning the art of artistic performance of peaceful scoring in basketball, as well as to identify the differences of different scoreboard heights in the results of learning the art of artistic performance of peaceful scoring in basketball between the experimental and control groups. The researcher assumed that there are statistically significant differences between the pre- and post-tests in learning the art of performing the skills of peaceful scoring, and that there are statistically significant differences between the experimental and control groups in the post-tests, and in favor of the experimental group. The research sample included students of the first stage of the College of Physical Education and Sports Sciences at Kirkuk University. The researcher concluded that the educational program had a positive effect for both the control and experimental groups in the art of performing peaceful scoring, and the results were preferable to the experimental group.